2016
DOI: 10.1016/j.ijpara.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis of early enteromyxosis in turbot (Scophthalmus maximus): new insights into parasite invasion and immune evasion strategies

Abstract: 27Enteromyxum scophthalmi, an intestinal myxozoan parasite, is the causative agent of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 81 publications
1
55
0
Order By: Relevance
“…Differential regulation of processes associated with both the innate and the adaptive immune system in immune organs and at the site of infection is a common feature in natural and experimental infections in vertebrates (e.g., Alvarez Rojas et al, 2015;Babayan et al, 2018;Huang et al, 2016) and the gradual shift from the regulation of innate to adaptive immune processes can be observed in gene expression studies (Ehret, Spork, Dieterich, Lucius, & Heitlinger, 2017). Additionally, parasite infections cause differential expression of genes not directly related to an immune response, such as those involved in metabolic processes, tissue repair, or organ function and development (Alvarez Rojas et al, 2015;Babayan et al, 2018;Ronza et al, 2016;Zhang et al, 2017) and this has also been observed in the European eel Schneebauer et al, 2017). How A. crassus affects gene expression in the Japanese eel and what processes are modified upon infection have not yet been determined for any parasitic stage.…”
mentioning
confidence: 99%
“…Differential regulation of processes associated with both the innate and the adaptive immune system in immune organs and at the site of infection is a common feature in natural and experimental infections in vertebrates (e.g., Alvarez Rojas et al, 2015;Babayan et al, 2018;Huang et al, 2016) and the gradual shift from the regulation of innate to adaptive immune processes can be observed in gene expression studies (Ehret, Spork, Dieterich, Lucius, & Heitlinger, 2017). Additionally, parasite infections cause differential expression of genes not directly related to an immune response, such as those involved in metabolic processes, tissue repair, or organ function and development (Alvarez Rojas et al, 2015;Babayan et al, 2018;Ronza et al, 2016;Zhang et al, 2017) and this has also been observed in the European eel Schneebauer et al, 2017). How A. crassus affects gene expression in the Japanese eel and what processes are modified upon infection have not yet been determined for any parasitic stage.…”
mentioning
confidence: 99%
“…Regulation of epithelial cell proliferation in response to macroparasite infections is associated with a pro‐inflammatory immune response in murine intestines (Cliffe et al., ) and in teleost skin (Kania, Evensen, Larsen, & Buchmann, ), involving cytokines such as TNFα and IL‐1β. Furthermore, studies relate regulation of epithelial cell proliferation to IFN‐γ production, which in turn modulates interleukin synthesis by macrophages (Artis, Potten, Else, Finkelman, & Grencis, ; Cliffe et al., ), and IFN‐related pathways were upregulated and played a main role at systemic as well as intestinal level during enteromyxosis in gilthead sea bream (Davey et al., ) and turbot (Ronza et al., ). Previous studies found a local shift towards an anti‐inflammatory cytokine response at 64 dpi (Pérez‐Cordón et al., ), supporting the gene expression reported for 113‐day chronic exposure (Sitjà‐Bobadilla et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In gastrointestinal infections, direct alterations of the enteric nervous system also needs to be considered (Halliez & Buret 2015). In turbot Psetta maxima with entero myxosis, down-regulation of the neuropeptide Y-receptor NPY2R, a main regulator of appetite (Zou & Secombes 2011), has been reported in early stages of the infection (Ronza et al 2016). This observation is in agreement with the early onset of anorexia in Group A in the current trial, which was observed as early as 1 wk p.i.…”
Section: Discussionmentioning
confidence: 99%